Relationship between Levels of Religiosity and Nomophobia in UIN Raden Fatah Palembang Students - Suryati; Hartika Utami Fitri; Riska Deri (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to determine the relationship between the level of religiosity and anxiety about being away from smartphones (nomophobia) among students at Raden Fatah State Islamic University, Palembang. This research uses quantitative methods and there are 90 samples used. The data collection techniques used in this research were observation and questionnaires to determine the relationship between the level of religiosity and nomophobia. The results of this research are that the correlation value r_(calculate) between the level of religiosity and anxiety about being away from smartphones (nomophobia) shows a figure of -0.226, thus the value of r_(calculate) < r_(table) at a significance level of 5% (0.207). This shows that H0 is rejected and Ha is accepted, namely that there is a negative and significant relationship between the level of religiosity and anxiety about being away from smartphones (nomophobia) in students at UIN Raden Fatah Palembang